The Effect of Transformational Leadership, Work Environment, Internal Communication, and Organisational Commitment on Internal Service Quality at the Office of the Class III Airport Operator Unit of South Papua Province - Sirajudin, Sirajudin; Syauta, Jack Henry; Nurhayati, Mafizatun (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of transformational leadership, work environment, internal communication, and organizational commitment on the quality of internal services at the Class III Airport Operating Unit of South Papua Province. The research method used is quantitative with a survey approach, where data is collected through questionnaires from airport employees which are then analyzed using regression analysis. The research results show that these four variables have a positive and significant influence on internal service quality. Effective transformational leadership, a conducive work environment, good internal communication and strong organizational commitment contribute significantly to improving the quality of internal services at the airport. These findings provide practical implications for airport management to focus on improving these factors to improve the quality of services provided.